Antimicrobial stewardship: Australia. Issue 3 (5th September 2016) - Spigelman, Allan D; Rendalls, Shane; McLaws, Mary-Louise; Gray, Ashleigh
Abstract : Purpose: To provide an overview of the context for strategies to overcome antimicrobial resistance in Australia, which may provide valuable learnings for other jurisdictions. Design/methodology/approach: Non-systematic review of literature from websites of national, State and Territory health departments and interviews with key stakeholders for Australian strategies to reduce antimicrobial resistance. Findings: In July 2015 all states and territories in Australia adopted the National Antimicrobial Resistance Strategy 2015-2019, which is built on the World Health Organization (WHO) Policy Package to Combat Antimicrobial Resistance. This strategy represents "the collective, expert views of stakeholders on how best to combat antimicrobial resistance in Australia. It will also support global and regional efforts, recognising that no single country can manage the threat of antimicrobial resistance alone." It combines quantitative and qualitative monitoring strategies with frameworks and guidelines to improve management of the use of antimicrobial resistant drugs. Prior to this, health services and states developed and implemented initiatives aimed at monitoring and improving prescribing practices. Development of the National Strategy has encouraged and fostered debate within the Australian health system and a raft of new policy initiatives Research limitations/implications: Surveillance strategies are in place to monitor impact and trends at jurisdictional and sector levels. However, actual impact on antimicrobial resistance and prescribing practices remains to be seen as existing initiatives are expanded and new initiatives implemented. Practical implications: This overview of key Australian initiatives balancing quantitative and qualitative surveillance, accreditation, research, education, community awareness and price signals on antibiotic prescribing practices may be valuable to health systems in developing local strategies. Originality/value: We provide an up to date overview of the context, strategies and aims of antimicrobial stewardship in Australia